The Impact of Internet Access Contributing to Farmers' Welfare in Indonesia: A Case Study Based on National Socio-Economic Survey - Wardhana, Adhitya; Fauzy, M. Zidan; Anggana, Adrian Kevianta; Kharisma, Bayu (Signifikan: Jurnal Ilmu Ekonomi, 2024)
Research Originality: This study highlights the transformative role of digitalization, particularly the use of internet networks and mobile phones, in addressing these challenges and enhancing the welfare of farmers.Research Objectives: This research aims to analyze the impact of internet usage on farmers' welfare in Indonesia. Specifically, it examines how access to digital tools can bridge the knowledge gap in the agricultural sector and improve economic outcomes, focusing on regional disparities between Western and Eastern Indonesia.Research Methods: This study uses National Socio-Economic Survey (Susenas) data and the ordered probit model with marginal effects.Empirical Results: Farmers in the upper-middle expenditure group can leverage the Internet and mobile phones to access production information, markets, and farm credit, supported by better finances and education. In contrast, low-income farmers, particularly in eastern Indonesia, face barriers such as costs, limited infrastructure, and low digital literacy, hindering technology adoption to improve welfare.Implications: The government is expected to address this digital divide by accelerating the development of internet infrastructure in rural areas, improving digital literacy, subsidizing technological devices, and developing accessible agricultural applications.JEL Classification: D6, I24, L86, Q12